Panagiotis Lefakis (?-1940). The blind majestic obstetrician who had been loved by the Ottomans - Tsoucalas, Gregory; Kyrkoudis, Theodoros; Mourellou, Evangelia; Tentes, Ioannis; Fiska, Aliki (European Journal of Therapeutics, 2024)
Sometimes, during an era of clashes, appears a man to promote humanism. Such a man was Panagiotis Lefakis who dedicated his life to treat the helpless inhabitants of Dedeagats (later Alexandroupolis) regardless of nationality and religion. With studies in Constantinople and Paris he practiced general medicine and obstetrics in Thrace. Lefakis, completely lost his eyesight by cause of retinal detachment but continued his work. With the help of his daughter Elli, he was the most preferable physician among the Muslims, as his blindness was an advantage due to cultural reasons. Muslim families felt secure as a blind man could not offend a Muslim female patient or a pregnant woman. His skills and temper helped Lefakis to achieve greatness and although he had been accused by his countrymen, the Ottoman authorities recognized his contribution.